"¡Que le quieren dar veneno al señor arzobispo-virrey!" Historia de una conspiración dirimida por la Inquisición de la Nueva España (agosto de 1809-enero de 1810) - Mejía Chávez, Carlos Gustavo (El Colegio de México, A.C., 2018)
This article offers a historiographic interpretation on one chapter of the life and political activity of the Archbishop and Viceroy Francisco Xavier de Lizana y Beaumont, who was involved in the work of the Tribunal of the Holy Office of the Inquisition during the final months of 1809 and into January 1810. By examining an Inquisition document in the possession of the General National Archive, it can be seen that once Lizana y Beaumont became the head of the government of New Spain, he made the decision to rely on the ministers of the Inquisition Tribunal, following the rumors of a plot to assassinate him that was being organized by members of the Royal Accord. The fear that the rumors of the conspiracy were true led the Archbishop-Viceroy to request that the Tribunal, and not the Council of Safety and Good Order, examine the available testimony to determine the truth of the plot.